Analysis of asset classes through the business cycle - Dzikevičius, Audrius; Vetrov, Jaroslav (Business, Management and Economics Engineering, 2012)
This study was driven by the dissimilar performance characteristics displayed by asset classes over the business cycle. The authors aim to explore assets classes on the grounds of a scientific literature review and a statistical analysis. Business cycles are divided into four stages to explore broad movements in returns of asset classes and a possible existence of asymmetrical effects of determinants within stages. Six main asset classes were analysed: US stocks, EAFE stocks, Bonds, Gold, Real Estate and Commodities. Monthly data from February 1976 to August 2011 were used for the study. The article combines business cycle and asset allocation theories by adding valuable information about performance of asset classes during different phases of the business cycle. Using the OECD Composite Leading Indicator as a business cycle measure, the authors demonstrate that different assets classes have different return/risk characteristics over the business cycle. The article demonstrates how to use the business cycle approach for investment decision-making. The OECD Composite Leading Indicator can provide significant information on market expectations and the future outlook; hence, results of this study can help every investor improve his/her performance and risk management.